?AGRONOMIC AND QUALITY TRAITS OF SOME ELITE RICE GENOTYPES - ABBASI, FIDA MUHAMMAD; SAGAR, M. ASLAM; AKRAM, M.; ASHRAF, M. (Biological Sciences - PJSIR, 1995)
Four elite lines and a cultivar of rice (Oryza sativa L.) were evaluated for agronomic and some of the quality characteristics during 1992 at NARC, Islamabad. DR45 and DR48 out yielded the check variety, KS282 by produ- cing 18% and II % higher grain yield. The highest elongation ratio (after cooking) was exhibited by KS282 while the highest protein content (8.66%) was recorded for DR46. Productive tillers/hill showed the highest coefficient of variability (10.8%). Whereas flowering duration showed the lowest (0.61%). All the genotypes possessed similar grain quality. DR46 was ranked as inferior, in terms of paddy yield.